JAVMA News (Journal of the American Veterinary Medical Association, 2013)
Objective To evaluate the clinical use, indications, outcomes, and adverse reactions associated with allogenic whole blood transfusions in domestic rabbits (Oryctolagus cuniculus). Methods A retrospective cohort of client-owned rabbits receiving allogenic whole blood transfusions at a veterinary teaching hospital between 1993 and 2025 was identified. Signalment, transfusion indications and parameters, and survival to discharge were collected. Adverse reactions were graded based on canine and feline consensus guidelines including imputability and severity scores. Results 21 rabbits were included. The most common indication for transfusion was blood loss from liver lobe torsion (10 of 21 [48%]) or intraoperative blood loss (6 of 21 [29%]). Results from crossmatching, performed in 62% of cases (13 of 21), were negative in all cases. Adverse reactions occurred in 10 of 21 rabbits, with 14 total adverse reactions reported. Transfusion-associated dyspnea (5 of 21 [24%]) and transfusion-associated cardiac overload (5 of 21 [24%]) occurred most frequently. All reactions were classified as nonsevere (9 of 14 [64%]) or severe (5 of 14 [36%]) and assigned imputability scores of possibly (9 of 14 [64%]) or probably (5 of 14 [36%]) related to the transfusion. Overall survival to discharge was 57% (12 of 21). Conclusions Allogenic whole blood first transfusions in domestic rabbits appeared clinically effective and generally well tolerated, with improved PCV and no life-threatening complications. Rabbits had a higher rate of acute respiratory signs during or after transfusion compared to dogs or cats. Clinical relevance Whole blood transfusion was a feasible, potentially lifesaving treatment in critically ill rabbits. Future studies should prospectively collect data to better characterize transfusion reactions in this species and allow optimization of protocols.